Automated Diagnostics: Advances in the Diagnosis of Intestinal Parasitic Infections in Humans and Animals - Inácio, Sandra Valéria; Gomes, Jancarlo Ferreira; Falcão, Alexandre Xavier; Martins dos Santos, Bianca; Soares, Felipe Augusto; Nery Loiola, Saulo Hudson; Rosa, Stefani Laryssa; Nagase Suzuki, Celso Tetsuo; Bresciani, Katia Denise Saraiva (Frontiers in Veterinary Science, 2021)
The growing proximity of the coexistence between people and animals is of great importance for Public Health, with regard to the increased risk of exposure to infectious diseases, since the animals are carriers of more than 60 zoonotic agents. These diseases are included in the list of “Neglected Tropical Diseases” causing losses in countries with tropical and subtropical climates, as well as regions with temperate climates; they affect more than a billion people, on which a large part of the people are infected by one or more helminths, causing billions of dollars in losses every year. Some studies that are being carried out in search of a differentiated diagnosis, more sensitive and with a lower proportion of errors, are linked to the automated examination of gastrointestinal parasites, however, there are still some challenges to be worked on for a good identification of the parasites, as a protocol that allows the elimination of most of the debris in the sample, an adequate coloration of the parasite structures, in addition to a robust image database. Therefore, our objective was to show, in a critical way, data about the current techniques of automated diagnosis of gastrointestinal parasites in fecal samples and their evolution.